Euphemism in the Instagram Captions of Lambe Turah: A Semantics Approach - Aulia Juli Saputri; Anna Riana Suryanti Tambunan; Fauziah Khairani Lubis (English Department - University of Sultan Ageng Tirtayasa, 2021)
Lambe turah as the most popular anonymous accounts on social media in Instagram, discusses celebrity life and viral events, demanded avoid misinterpretation or any lawsuits to prevent of losing their face. To avoid it, Lambe Turah used euphemism. Through semantic approach, this study attempts at analyzing the types of euphemism in Lambe Turah Instagram captions. The study was conducted using a descriptive qualitative method and the data used were the written words that appeared in Lambe Turah Instagram captions. The result of this study shown that the most frequently types of euphemism were found was clipping. In conclusion, euphemism not only continually renames items and repackages them to